Quantifying Variation in Wetland Composition and Configuration for Landscape-Scale Reclamation Planning - Evans, Ian Scott (University of Waterloo, 2016)
Widespread loss and degradation of wetland ecosystems resulting from human land use highlights the need for a reclamation strategy (i.e converting developed land back to its original state) that can sustain ecosystem services provided by wetlands. Successful reclamation planning requires an understanding of the linkages between individual wetlands and the structure of their surrounding landscapes. A parsimonious set of representative metrics, measuring the composition and configuration of wetland landscapes in southern Alberta, was identified using variable reduction procedures, and then related to anthropogenic disturbance with the intent of establishing a continuum of reference conditions for structure of landscapes at varying disturbance levels. The spatial configuration of low-disturbance and high-disturbance landscapes were significantly different from other landscapes, suggesting that a reference condition approach would be appropriate for landscape-scale reclamation. Aggregation metrics quantifying the connectivity, proximity, isolation, contagion, and interspersion of wetland patches were the most commonly identified measures of wetland configuration independent of wetland-proportion in the landscape. Metric values differed significantly between Natural Regions, indicating that reference conditions will likely vary depending on spatial location. Selection and values of representative metrics is impacted by data quality. A framework for wetland reclamation is proposed with the caveat that future research will first need to assess the relationships between landscape characteristics and site-level topography and biophysical conditions.
Keywords: wetlands; reclamation; GIS; remote sensing; landscape ecology